Phrasebook in Text Typology: a Type of Textbook or an Independent Type of Text? - M. A. Sokoljuk (Дискурс, 2024)
Introduction. A phrasebook as a type of text is aimed at providing the basics of communication in situations when the knowledge of a foreign language is absent. It can not be classified as a type of a dictionary, textbook or manual for the development of speaking skills. The article examines the problem of determining the status of a phrasebook in the typology of text types. The study is aimed at a diachronic analysis of the texts and structure of phrasebooks to identify features that unite a phrasebook with a textbook, as well as to determine the properties inherent only to a phrasebook, allowing it to be distinguished as an independent type of text. The lack of works that consider the problem of determining the status of a phrasebook determines the relevance of the study.Methodology and sources. The research material – the texts of German-Russian and Russian-German phrasebooks of the XVIII–XXI centuries, covering the time period from 1795 to 2011, which were created both for teaching the German or Russian language, and for practical use during travel. The general (educational and tourist) phrasebooks were chosen because of the fact that they reflect different aspects of interaction between representatives of language communities in predetermined situations.Results and discussion. The comparison has shown that a phrasebook is an independent type of text, at different stages of its historical development having more or less similar features with a textbook, dictionary and a manual for the development of oral speech skills, but differing significantly from them. In the course of its historical development, the cohesive connections between the linguistic units of the phrasebook weaken: from a book containing coherent and logical dialogues on various topics (XVIII–XIX centuries), the phrasebook turns into a manual with a set of thematically organized template phrases and lists of words (late XX–XXI centuries).Conclusion. The phrasebook, thus, is a type of text that is closely related to the era of creation, which is reflected not only in the theme and structure, but also in the strength of the cohesive connections of the linguistic units that make up the phrasebook.